BRITISH COUNCIL PODCAST APPS TO IMPROVE STUDENTS’ LISTENING COMPREHENSION - Ningtias, Fitria Cahya; Prastikawati, Entika Fani; Wahyuni, Sri (Wiralodra English Journal, 2021)
This study investigated the effectiveness of British Council Podcast Apps to improve students’ listening comprehension of students in senior high school. For that purpose, this study carried out a quasi-experimental research design by applying pre-test and post-test. There were two classes consisting 72 students (36 students are in control group; 36 students in experimental) of senior high school. This study took place in SMA Negeri 9 Semarang, Indonesia. In collecting the data, an adopted listening comprehension test was used in pre-test and post-test. SPSS 23 was then used to analyze the mean, standard deviation and t-test calculation. The result showed that British Council Podcast Apps is effective to improve the students’ listening comprehension. This study implies that utilizing technology in listening class is important to support the students achieve the maximum goal of learning as well as the improvement of their listening comprehension.